Upaya Peningkatan Penghasilan Ibu Rumah Tangga dan PKK dengan Memanfaatkan Perkebunan Ubi Sebagai Aset Desa terhadap Masyarakat Desa Benteng Provinsi Aceh - Rahmad Safitri; Sharfinna Hafizah; Salma Ummul Khair; Tachta Khalil; Suryani Suryani; Muhammad Rifqi; Iqfariana Iqfariana; Lisa Ulandari (Fakultas Ekonomi dan Bisnis Islam - IAIN Lhokseumawe, 2023)
In Indonesia, cassava, or cassava,bodin has important economic significance compared to other tubers. one of them is because cassava has very strong resistance in various climates, from planting to harvesting cassava also does not require large capital. Processed products from cassava can be found easily in Benteng Village, but the community ignores this one asset that has great potential to improve the community's economy. This community service aims to assist the community in optimizing sweet potato plantations to increase household income. This activity aims to provide efforts to develop assets on sweet potato plantations in Benteng village using the ABCD (Asset, Bassed, Community, Development) method, namely an approach that looks at the condition of the community in terms of the assets and potential possessed by the community. Using this method can improve the economy in Benteng village through sweet potato or cassava plantations. Based on the results of activities to increase the income of housewives and PKK, it can be concluded that the innovations and business ideas implemented can be a solution to increase the income of housewives in Benteng village.